Empires of light : vision, visibility and power in colonial India - Dinkar, Niharika (Rethinking art's histories., 2019)
Light was central to the visual politics and imaginative geographies of empire, even beyond its role as a symbol of knowledge and progress in post-Enlightenment narratives. This book describes how imperial mappings of geographical space in terms of 'cities of light' and 'hearts of darkness' coincided with the industrialisation of light (in homes, streets, theatres) and its instrumentalisation through new representative forms (photography, film, magic lanterns, theatrical lighting). Cataloguing the imperial vision in its engagement with colonial India, the book evaluates responses by the celebrated Indian painter Ravi Varma (1848-1906) to reveal the centrality of light in technologies of vision, not merely as an ideological effect but as a material presence that produces spaces and inscribes bodies.